2023
DOI: 10.3390/ani13081349
|View full text |Cite
|
Sign up to set email alerts
|

Age Rather Than Supplementation with Oat β-Glucan Influences Development of the Intestinal Microbiota and SCFA Concentrations in Suckling Piglets

Abstract: The effects of early supplementation with oat β-glucan during the suckling period on piglet gut microbiota composition, concentrations of short-chain fatty acids, and gut physiological markers were assessed. Fifty piglets from five litters, balanced for sex and birth weight, were divided within litters into two treatment groups: β-glucan and control. Piglets in the β-glucan group received the supplement three times/week from day 7 of age until weaning. Rectal swab samples were collected from 10 piglets per tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The gut microbiota is a complex system that plays an important role in health and immunity in pigs [ 9 , 10 , 11 , 12 , 13 ]. It comprises a diverse population of bacteria and other microorganisms [ 14 , 15 ], and its composition and quantitative and qualitative variations are influenced by both environmental and host genetic factors [ 16 , 17 , 18 , 19 , 20 ]. Previous studies demonstrated a link between microbial profiles and nutritional and productivity parameters [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is a complex system that plays an important role in health and immunity in pigs [ 9 , 10 , 11 , 12 , 13 ]. It comprises a diverse population of bacteria and other microorganisms [ 14 , 15 ], and its composition and quantitative and qualitative variations are influenced by both environmental and host genetic factors [ 16 , 17 , 18 , 19 , 20 ]. Previous studies demonstrated a link between microbial profiles and nutritional and productivity parameters [ 21 ].…”
Section: Introductionmentioning
confidence: 99%